Immigration and the UK economy after Brexit - Jonathan Portes (Global Labor Organization (GLO), 2021)
I review trends in migration to the UK since the Brexit referendum, examining first the sharp fall in net migration from the EU that resulted, and then the recent more dramatic exodus of foreign-born residents during the covid-19 pandemic. I describe the new post-Brexit system, and review studies which attempt to estimate both the impact on future migration flows and on GDP and GDP per capita. Finally, I discuss the wider economic impact of the new system and some of the policy implications.
Keywords: E24; J24; J61; M53; 330; Immigration; Great Britain; productivity